Re-Considering the Unity of Architecture and Human Well-Being - Susanne Siepl-Coates (Oz, 2013)
Over many centuries people have shared the belief that there are significant connections between human health and the physical environment. Based on this belief, architects of the early Modern Movement such as Richard Neutra (Lovell ‘Health House’), Johannes Duiker (Zonnestraal Sanatorium), and Alvar Aalto (Paimio Sanatorium) have designed buildings with the explicit intention of positively impacting human health and well-being. In fact, improving human health was one of the primary tenets of the Modern Movement.